2012
DOI: 10.1155/2012/973279
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Acute Pancreatitis Probably Induced by Rosuvastatin Therapy: A Case Report

Abstract: Context. Approximately 1.4–2% of all cases of acute pancreatitis are drug related in general population. The literature on statin-induced pancreatitis consists primarily of anecdotal case reports. We report a case of possible rosuvastatin-induced pancreatitis. Case Report. A 67-year-old female presented with progressively worsening abdominal pain and vomiting for 7 days. Home medications included rosuvastatin and clonidine. CT scan of abdomen, with intravenous contrast, showed findings consistent with acute pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
(16 reference statements)
0
9
0
Order By: Relevance
“…It indicates that only patients still continuing to ingest rosuvastatin might have the odds, but those who once ingested rosuvastatin but are not ingesting it now do not have the odds of acute pancreatitis. To date, only two cases have been reported that rosuvastatin could be associated with acute pancreatitis, including one case having re-challenge confirmation of a causal relationship [6], and another case with probable association due to no receiving rechallenge test [5]. To the best of our knowledge, this is the first population-based case-control study to test the association focusing on rosuvastatin use only and acute pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It indicates that only patients still continuing to ingest rosuvastatin might have the odds, but those who once ingested rosuvastatin but are not ingesting it now do not have the odds of acute pancreatitis. To date, only two cases have been reported that rosuvastatin could be associated with acute pancreatitis, including one case having re-challenge confirmation of a causal relationship [6], and another case with probable association due to no receiving rechallenge test [5]. To the best of our knowledge, this is the first population-based case-control study to test the association focusing on rosuvastatin use only and acute pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
“…Its rare adverse effects include myopathy, elevation of creatine kinase and liver function test abnormalities [2][3][4]. In addition, two cases have been reported that rosuvastatin could be associated with acute pancreatitis [5,6]. The U.S. Food and Drug Administration has also reported that from 2003 to 2014, 483 people (0.84%) had pancreatitis among 57,750 people reporting to have side effects when ingesting rosuvastatin [7].…”
Section: Introductionmentioning
confidence: 99%
“…As such, their remains a dearth of concrete experimental evidence regarding the precise mechanism of action for the reported cases of statin-induced pancreatitis. Interestingly, the majority of documented instances in which statins have been reintroduced, demonstrate reproducibility of acute pancreatitis and/or symptoms consistent with this diagnosis [8,13,[19][20][21] . However, these findings have not been universal as Belaiche and colleagues have documented a patient who tolerated pravastatin prior to and following an episode of atorvastatin-induced pancreatitis [22] .…”
Section: Discussionmentioning
confidence: 99%
“…Other adverse effects have been reported in the context of case-report studies, such as pemphigoid,7 erythema multiforme,8 erythromelalgia,9 recurrent pancreatitis,10 11 thrombocytopaenia,12 gynaecomastia,13 as well as short-term memory loss 14. These unusual adverse effects are currently anecdotal and occurred with doses of rosuvastatin between 5 and 40 mg daily.…”
Section: Discussionmentioning
confidence: 99%